Correlation Between Depression Level and Red Blood Cell Distribution Width (RDW) and Erythrocyte Sedimentation Rate (ESR) in Chronic Kidney Disease (CKD) Patients Undergoing Regular Hemodialysis at Haji Adam Malik General Hospital Medan - Prianto, Dwi; Lubis, Wika Hanida; Nasution, Alwi Thamrin (Journal of Society Medicine, 2023)
Introduction: Chronic Kidney Disease are related to inflammation and stress levels therefore depression is a predictor that will increase the morbidity and mortality of patients with chronic kidney disease undergoing hemodialysis. Method: This research is an analytical study with a cross-sectional design which carried out in Januari until February 2023, at Hemodialysis Installation of RSUP. H. Adam Malik. To analyze the correlation between the Depression Level and Red Blood Cell Distribution Width (RDW) and Erythrocyte Sedimentation Rate (ESR), the Pearson correlation test was used if the data was normally distributed. If the data is not normally distributed, Spearman's correlation test is performed. Statistical analysis using 95% confidence level (p<0.05). Results: In this research, demographic characteristics of 85 patients with mean age of the patients was 49.56 years old with a standard deviation of 13.46. Based on Spearman rho test it was found that there was a significant correlation between RDW and the BDI II score with p value 0.003. The degree of correlation or r value was 0.318. This indicates that there is a weak correlation between the RDW score and the BD II score. Based on Pearson test it was found that there was a significant correlation between ESR and the BDI II score with p value 0.009. The degree of correlation or r value was 0.280. This indicates that there is a weak correlation between the ESR value and the BD II score. Conclusion: Level of depression were found to be correlated with Red Blood Cell Distribution Width (RDW) and Erythrocyte Sedimentation Rate (ESR) in CKD patients whose undergoing regular hemodialysis.